2011
DOI: 10.1038/mt.2011.100
|View full text |Cite
|
Sign up to set email alerts
|

Neural Stem Cell-based Cell Carriers Enhance Therapeutic Efficacy of an Oncolytic Adenovirus in an Orthotopic Mouse Model of Human Glioblastoma

Abstract: The potential utility of oncolytic adenoviruses as anticancer agents is significantly hampered by the inability of the currently available viral vectors to effectively target micrometastatic tumor burden. Neural stem cells (NSCs) have the ability to function as cell carriers for targeted delivery of an oncolytic adenovirus because of their inherent tumor-tropic migratory ability. We have previously reported that in vivo delivery of CRAd-S-pk7, a glioma-restricted oncolytic adenovirus, can enhance the survival … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
147
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 113 publications
(157 citation statements)
references
References 28 publications
6
147
0
4
Order By: Relevance
“…NPCs injected systemically into healthy animals were in fact never found in the CNS, while exclusively accumulating (and persisting only for a short period) in peripheral organs (Pluchino et al, 2003). Specific homing of transplanted NPCs has been shown, so far, in experimental brain stroke (Chu et al, 2003;Lindvall and Kokaia, 2011), SCI (Takeuchi et al, 2007), epilepsy (Chu et al, 2004;Hattiangady et al, 2008), HD (Lee et al, 2006), and glioblastoma (Aboody et al, 2000;Ahmed et al, 2011).…”
Section: Homing and Extravasationmentioning
confidence: 99%
“…NPCs injected systemically into healthy animals were in fact never found in the CNS, while exclusively accumulating (and persisting only for a short period) in peripheral organs (Pluchino et al, 2003). Specific homing of transplanted NPCs has been shown, so far, in experimental brain stroke (Chu et al, 2003;Lindvall and Kokaia, 2011), SCI (Takeuchi et al, 2007), epilepsy (Chu et al, 2004;Hattiangady et al, 2008), HD (Lee et al, 2006), and glioblastoma (Aboody et al, 2000;Ahmed et al, 2011).…”
Section: Homing and Extravasationmentioning
confidence: 99%
“…Neural stem cell-mediated enzyme prodrug therapy (NMEPT) is an emerging field that holds promise for treatment of many invasive types of cancer, including glioma, neuroblastoma, medulloblastoma, metastatic breast cancer, and melanoma [7][8][9][10][11][12][13][14][15]. Approaches similar to NMEPT but using mesenchymal stem cells (MSCs), induced pluripotent stem cells (iPSCs), or other types of stem cells are also under investigation [16,17]. A key characteristic of many of these stem cells is that they exhibit tumor-specific migration to distant tumors located intracranially or extracranially [18].…”
Section: Introductionmentioning
confidence: 99%
“…The therapeutic effi cacy of NSC-CRAds was tested in a subcutaneous tumor model, where the volume of tumors that received virus loaded NSCs reduced signifi cantly compared to tumors that received viruses alone [ 66 ]. Another study from the same group showed a similar effect in orthotopic glioma model, where NSC-CRAd inhibited tumor growth, and increased the median survival by 50 % [ 67 ]. In a comparative study by the same group, the potential of NSCs and other stem cells types (MSCs) as carriers for CRAds was assessed and NSCCRAds that were administered intracranially in an orthotopic glioma model significantly prolonged the survival of tumor bearing animals and displayed superior therapeutic effi cacy in intracranial tumors [ 68 ].…”
Section: Viruses/oncolytic Viral Particlesmentioning
confidence: 93%